Birth outcomes among US women with intellectual and developmental disabilities. Issue 3 (July 2017) - Akobirshoev, Ilhom; Parish, Susan L.; Mitra, Monika; Rosenthal, Eliana
Abstract: Background: Women with intellectual and developmental disabilities (IDD) are bearing children at increasing rates. However, there is very little research about pregnancy experiences and birth outcomes among women with IDD. No studies to date have examined birth outcomes with a US population-based sample. Objective: The main objective was to estimate the national occurrence of deliveries in women with IDD and to compare their birth outcomes to women without IDD. Methods: We examined the 2007–2011 Nationwide Inpatient Sample of the Healthcare Cost and Utilization Project to compare birth outcomes in women with and without IDD. Birth outcomes included preterm birth, low birth weight, and stillbirth. Multivariable regression analyses compared birth outcomes between women with and without IDD controlling for race/ethnicity, maternal age, household income, health insurance status and type, comorbidity, region and hospital location, teaching status, ownership, and year. Results: Of an estimated 20.6 million deliveries identified through the HCUP 2007–2011 data 10, 275 occurred in women with IDD. In adjusted regression analyses, women with IDD compared to those without IDD were significantly more likely to have preterm birth (OR = 1.46; 95%CI: 1.26–1.69, p < 0.001), low birth weight (OR = 1.61, 95%CI: 1.27–2.05, p < 0.001), and stillbirth (OR = 2.40, 95% CI: 1.70–3.40, p < 0.001). Conclusion: This study provides a first examination of the birth outcomes among women with IDD in the United States using a largest population-based sample. There are significant differences in birth outcomes between women with and without IDD. Understanding the causes of these differences and addressing these causes are critical to improving pregnancy outcomes among women with IDD.